2016
DOI: 10.1021/acs.iecr.5b04034
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on the Acid Hydrolysis ofCenchrus ciliarisParticles for the Production of Xylose and Other Monosaccharides

Abstract: An experimental study on the acid hydrolysis of Cenchrus ciliaris particles was conducted. Input variables included particle size of the raw material (<0.053 mm and 0.16 mm), sulfuric acid concentration (0.05 and 0.15 M), and reaction temperature (120−150 °C). Output variables included the concentrations of xylose, glucose, arabinose, and furfural in the aqueous solution. Five chemical reactions involving the hydrolysis of the Cenchrus ciliaris particles and the decomposition of the monosaccharides were propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A similar trend of rise and fall in glucose yield was also observed by [12] in their kinetic study on acid hydrolysis Cenchrus ciliaris. Reference [13] obtained optimum condition for wheat bran pre-treatment to be: acid concentration of 1.75% (w/v), at 190 °C for 10 min.…”
Section: Effect Of Process Parameters On Hydrolysis Of Cowpea Hullsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar trend of rise and fall in glucose yield was also observed by [12] in their kinetic study on acid hydrolysis Cenchrus ciliaris. Reference [13] obtained optimum condition for wheat bran pre-treatment to be: acid concentration of 1.75% (w/v), at 190 °C for 10 min.…”
Section: Effect Of Process Parameters On Hydrolysis Of Cowpea Hullsupporting
confidence: 81%
“…A similar trend was also observed with 15% acid concentration which gave activation energy 82.204 KJ for K 1 and 60.499 KJ for K 2 . Reference [12], obtained activation energy of 24KJ/mol for glucose formation in a acid hydrolysis of Cenchrus ciliaris particles. Reference [16], obtained the activation energy value of 29.96KJ for glucose production form cassava root sieviate using 10% acid concentration.…”
Section: Kinetic Studymentioning
confidence: 99%
“…Therefore, the hydrolysis rate of various monosaccharides is arabinose, rhamnose and xylose. The results show that the hydrolysis rate of monosaccharide is directly proportional to its removal efficiency, 42 In a study on a hydrolysis model of the three pentoses, the fastest hydrolysis was observed for methyl pyran arabinose with glycosylates in hemicellulose, 43 which led to the complete removal of arabinose at 160 C, while rhamnose could be completely removed at 170 C. To sum up, increasing the temperature can make the slow removal stage and the fast removal stage complete the reaction rapidly during the heating process, and improve the removal rate of arabinose, that is, the complete removal time is shortened from 120 min to 30 min.…”
Section: Effect Of Hydrolysis Degree (Temperature and Time) On Ph Of ...mentioning
confidence: 95%
“…Co-culture of two strains also has its own problem, including the destructive interactions between strains. 3,4,6,17 Furthermore, conversion of high sugar levels was rarely considered in PMBR, which could decrease the needed footprint and cost. Immobilization could be used as a helpful method to neutralize the different inhibitions such as interactions and high compound levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recombinant strains cannot perform well on an industrial scale. Co-culture of two strains also has its own problem, including the destructive interactions between strains. ,,, Furthermore, conversion of high sugar levels was rarely considered in PMBR, which could decrease the needed footprint and cost. Immobilization could be used as a helpful method to neutralize the different inhibitions such as interactions and high compound levels. , In our previous study, the effect of various cultivation strategies using P. stipitis and Z. mobilis strains was studied, among which the sequential-co-immobilized cultivation via CA beads was selected as having synergistic interaction.…”
Section: Introductionmentioning
confidence: 99%